Structural Inertia and Organizational Change - Hannan, Michael T.; Freeman, John (American Sociological Review, 1984)
Considers structural inertia in organizational populations as an outcome of an ecological-evolutionary process. Structural inertia is considered to be a consequence of selection as opposed to a precondition. The focus of this analysis is on the timing of organizational change. Structural inertia is defined to be a correspondence between a class of organizations and their environments. Reliably producing collective action and accounting rationally for their activities are identified as important organizational competencies. This reliability and accountability are achieved when the organization has the capacity to reproduce structure with high fidelity. Organizations are composed of various hierarchical layers that vary in their ability to respond and change. Organizational goals, forms of authority, core technology, and marketing strategy are the four organizational properties used to classify organizations in the proposed theory. Older organizations are found to have more inertia than younger ones. The effect of size on inertia is more difficult to determine. The variance in inertia with respect to the complexity of organizational arrangements is also explored. (SRD)